Simulation of bulk density distribution of wheat in silos by finite element analysis. (June 2018) - Gao, Mengyao; Cheng, Xuduo; Du, Xiaocui
Abstract: Bulk density is a critical parameter for predicting grain pressures in silos, determining the resistance to airflow, and estimating the grain mass in storage bins, so studying the bulk density distribution is critical for the storage security of wheat during storage. To investigate the bulk density distribution of the wheat bulk stored in an axisymmetric steel silo with flat bottom, the Modified Cam-Clay model was applied to calculate the bulk density of wheat at four different moisture levels at different depth and radius of the silo. The results showed that the bulk density of wheat at different depth was not uniform and it increased with increasing grain depth but decreased near the wall-bottom of silos. Moreover, it was found that the bulk density of the wheat decreased with increasing radius at the same depth and the same moisture content. Furthermore, the mean bulk density of a layer of wheat was negatively correlated with moisture content at the same grain depth and approached a plateau value when the wheat was close to the bottom of the silo at the same moisture content. The bulk density was adequately fitted as a function of the grain depth and moisture content in silos. Highlights: The Modified Cam-Clay model can adequately predict the bulk density distribution of the wheat in silos. The bulk densities of wheat in silos increased with increasing grain depth but decreased near the corner of silos. Mean bulk density of a layer of wheat was negatively correlated with radius and moisture content. Mean bulk density of a layer of wheat approached a stable maximum value when the wheat was near the bottom of silos. The proposed function adequately predicted the mean bulk density with respect to depth and moisture content.